Rethinking academic literacies. A conceptual development based on teaching practice. Issue 6 (18th August 2018) - Canton, Ursula; Govan, Michelle; Zahn, Daniela
ABSTRACT: Academic Literacies, the most influential conceptual framework for writing practitioners at UK universities, is closely related to widening participation. At the same time, writing support is often justified with the argument that written communication is among the most important employability skills for graduates. While these concepts are often used simultaneously, their underlying premises are not necessarily congruent. This paper reflects on a writing intervention that highlighted the difficulties that can arise from a seeming 'pick and mix' use of these two frameworks, Academic Literacies and writing as an Employability Skill. Based on this analysis of the practice of teaching writing at a post-92 university, it establishes the need for an expanded, theoretical framework for writing support.